Bio-based composites of sago starch and natural rubber reinforced with nanoclays - Jareerat Ruamcharoen; Ruszana Munlee; Lapporn Vayachuta; Polphat Ruamcharoen (eXPRESS Polymer Letters)
Sago starch (SS) was blended with natural rubber (NR) using nanoclays, namely montmorillonite (MMT), kaolinite (KAO), and kaolinite modified by dimethyl sulfoxide (KAO-D) to enhance its physical and mechanical properties. Each nanoclay was incorporated at 2, 4, 6, and 8 wt%, respectively. The SS80NR20 (80 wt% of sago starch and 20 wt% of natural rubber) biocomposites were characterized by solubility of water, water vapor transmission, mechanical and thermal properties. The constituent interaction and morphology of the SS80NR20 biocomposites were also presented by using X-ray diffraction (XRD) technique and scanning electron microscope (SEM). The findings demonstrated that the inclusion of clays significantly improved both the water resistance and tensile properties when compared to the SS80NR20 blend. In the SS80NR20 biocomposites, MMT at 6 wt% exhibited the lowest moisture content, solubility in water, and water vapor transmission. As the amount of nanoclay in the biocomposites increased, their tensile strength dramatically increased whilst their strain at break had a tendency to diminish. Strong interaction by establishing the intercalated structure of MMT, and KAO within SS80NR20 biocomposites were attributed to both physical and mechanical properties, while the weak interaction at the interface of SS and NR was attributed to KAO-D.